Analisis Kualitas Pelayanan Kesehatan Yang Menggunakan BPJS dan Non-BPJS Di Darmawan Dental Clinic Sangatta Ditinjau Dari Perspektif Ekonomi Islam - Zulkifli Zulkifli; Imrona Hayati; Totok Adhi Prasetyo (Jurnal Ekonomi dan Bisnis Digital, 2025)
In Islam, healthcare is a sharia obligation based on the principles of justice and mutual assistance, as stated in Surah An-Nahl, verse 90. However, the implementation of BPJS (Social Security Administering Body) often faces challenges, including procedural constraints, limited facilities, and a suboptimal doctor-to-patient ratio, which often leads to negative perceptions among patients. These issues lead to significant differences in satisfaction levels between BPJS and non-BPJS patients. Therefore, this study was designed to analyze the quality of healthcare services for both groups of patients at Darmawan Dental Clinic Sangatta, from an Islamic economic perspective. This study used a mixed method through a descriptive quantitative approach. Data were collected from 30 BPJS patients and 30 non-BPJS respondents through questionnaires. The results showed that, in general, both groups of patients rated the quality of care at the clinic as good. Although there were some differences in expectations and experiences, further analysis did not reveal significant differences in perceived service quality. The main difference found was in the types of services available; BPJS patients cannot access all types of care available to non-BPJS patients.